Systematic quantitative modeling of the natural history of Aicardi syndrome: a cross sectional study of 245 published cases - Urban, Oliver Y.; Driedger, Jan Henje; Garbade, Sven; Hoffmann, Georg F.; Kölker, Stefan; Ries, Markus; Syrbe, Steffen (Orphanet journal of rare diseases, 2024)
Aicardi syndrome is a rare epileptic encephalopathy, almost exclusively affecting girls. It was first described as a triad of infantile spasms, chorioretinal defects and agenesis of the corpus callosum. The etiology remains unknown and there is uncertainty on best practice therapy and outcome. We aimed at defining quantitative clinical endpoints that will inform future research and clinical trials.